Student Workbook and Activity Guide for Duffy's Collision Repair Fundamentals - Duff, James E. (Thomson, 2006)
This all new textbook was written and illustrated to introduce readers to automotive collision repair. Collision Repair Fundamentals stresses the repair of minor body damage and repainting, as well as advanced repairs such as frame straightening and structural